Augmented Reality Development for Creating Interactive Experiences in Tourism Places - Pranata, Caraka Aji; Filza, Muhammad Fairul; Tanudidjaja, Miquel Jan (Politeknik Negeri Batam, 2025)
Technology, hardware and software are developing rapidly as time goes by. One of the results of this rapid technological development is Augmented Reality (AR) technology. Current tools in augmented reality (AR) were offered by Vuforia Software Development Kit (SDK). However, with the rapid development of Unity Engine, now we can integrated OpenCV in Unity Engine. This integration presents ideas for the development of AR technology. This study uses an approach that uses research and development (R&D) methodology. The model that will be used is the utilization of the ADDIE development framework. We encountered three main problems, problems faced are